Ten simple rules for helping newcomers become contributors to open projects - Sholler, Dan; Steinmacher, Igor; Ford Robinson, Denae; Averick, Mara; Hoye, Mike; Wilson, Greg (PLoS Computational Biology, 2019)
To survive and thrive, a community must attract new members, retain them, and help them be productive. As openness becomes the norm in research, software development, and education, knowing how to do this has become an essential skill for principal investigators and community managers alike. A growing body of knowledge in sociology, anthropology, education, and software engineering can guide decisions about how to facilitate this.